Milton Friedman a biography - Ebenstein, Alan O (Palgrave Macmillan, 2007)
Chronicles the life of economist Milton Friedman, discussing his contributions to economic theory, his role as a commentator and pundit, his efforts to reduce government and promote personal freedoms, and other related topics.